Supply chain as strategic asset : the key to reaching business goals - Sehgal, Vivek (Hoboken, N.J. : John Wiley & Sons, 2011)
'The book starts by summarizing the current literature on business, functional (supply chain), and technology strategies. Then, it establishes a case for why none of these strategies in isolation can create the competitive advantage needed to achieve the goals of the business and why they must be aligned and must work together to be effective. Every argument in the book is supported with cases from the industry. Some of the cases I have relied heavily are Wal-mart (business strategy of being a'price leader' drives supply chain strategy to reduce costs), Cemex (business strategy of'differentiation' drives supply chain that is customer centric), and several other industry examples (Avon, Tyco, Rubbermaid, etc.) as they fit the argument being made at the time. The book concludes by consolidating the lessons learned and implementation guidance on how the 3 strategies and be pulled together resulting in a strategic roadmap.'--
Includes bibliographical references and index.
Keywords: Business logistics; Strategic management